2020
DOI: 10.1108/jacpr-05-2020-0509
|View full text |Cite
|
Sign up to set email alerts
|

Measuring aggression in the South Asian context: the development and psychometric assessment of the Urdu aggression questionnaire

Abstract: Purpose Aggression is an undesirable behavior that assaults traditions norms, morals and standards of ethics practiced in society. To address the scarceness of identification tools and for evidence-based interventions in Pakistan, the purpose of this study is to determine the extent to which aggression is prevalent in Pakistan’s people by newly developed self-reported questionnaires in the Urdu language designed after reviewing the cultural and social perspectives of the society. Design/methodology/approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Sohanjana Antibullying Intervention is a low-cost teachers' professional development program and evidence-based research intervention, which is specially designed for low to middle income countries like Pakistan, and aims to control both traditional and cyber forms of bullying to address the issues at their root. Majeed and Malik (2017) suggested that anger expressions are influenced by societal practices in Pakistan and differences of expressions and acceptance of aggression in different communities vary greatly and using similar tools and skills to address aggression and bullying among different cultures may not provide successful results (Siddiqui, Kazmi & Ahmed, 2021). Because of these highlighted factors, components are structured with social, cultural, and religious values in mind and for multilingual settings to accommodate teachers from different regions of Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…Sohanjana Antibullying Intervention is a low-cost teachers' professional development program and evidence-based research intervention, which is specially designed for low to middle income countries like Pakistan, and aims to control both traditional and cyber forms of bullying to address the issues at their root. Majeed and Malik (2017) suggested that anger expressions are influenced by societal practices in Pakistan and differences of expressions and acceptance of aggression in different communities vary greatly and using similar tools and skills to address aggression and bullying among different cultures may not provide successful results (Siddiqui, Kazmi & Ahmed, 2021). Because of these highlighted factors, components are structured with social, cultural, and religious values in mind and for multilingual settings to accommodate teachers from different regions of Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…The trainers considered the importance of such trainings and suggested that such trainings be integrated into curricula for pre-service and in-service teacher courses. In a country like Pakistan, the field of applied research often overlooks preventive intervention programs aimed at controlling aggression and conduct issues among children (Siddiqui et al, 2021b). Nevertheless, participant responses have strongly indicated the urgent need to rethink and redesign educational and professional development courses in order to effectively address the escalating issue of antisocial aggressive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical research should also be conducted to accurately assess the effectiveness of such interventions. In Pakistan, the national language and language of instruction in most educational institutions is Urdu; therefore, for evidence-based research, it is recommended that tools developed, adopted or adapted in the local language be used to facilitate instructors and children to provide accurate data according to Siddiqui et al (2021b).…”
Section: Uniformity In Curriculumsmentioning
confidence: 99%
“…(2017), no significant differences among the female and male participants in terms of EI and SE were established in this study. It is presumed that despite the differences in the upbringing of both female male and male children in Pakistan's context (Siddiqui et al., 2020), differences in the EI and SE were not established among the participants with different genders.…”
Section: Instrumentsmentioning
confidence: 99%